Extending the capability of component digital threads using material passports. (3rd February 2023) - Paramatmuni, Chaitanya; Cogswell, Daniel
Abstract: Nuclear and aerospace applications are critical to safety that demand quality metallic components. The cost of failure in these components far exceed that of repair or replacement. Thus, it is necessary to track the evolution of material properties at critical locations of the component geometry during manufacturing and in-service to avoid premature failures. The digital thread/twin (DTh/DT) paradigm shows promise for its ability to interact with components by monitoring their production. This capability of the DTh can be further extended by generating component specific unique identification document called material passport (MP). In addition to storing the manufacturing history and inspection records, the MP can be used to indicate remaining useful life estimations to guide component recyclability/reusability. The structure of the DTh and the corresponding MP depends on several factors. This article presents an overview of the nature of DThs/DTs for manufacturing based on the lengthscale of material property definitions employed in respective computational framework and the type of material purchase specification system implemented in the industry. Then, the possible structure, significance and challenges of realizing MPs that enable predictive maintenance and circular economy are discussed. The preliminary discussions indicate that the implementation of component specific DThs encompassing all the stages of manufacturing in conjunction with the generation of summary and detailed MPs at every stage improves data storage and accessibility within MPs and predictive maintenance capabilities of DThs. Finally, the landscape of standards used in MPs and DThs is addressed briefly.